Limited variability in the phytoplankton Emiliania huxleyi since the pre-industrial era in the Subantarctic Southern Ocean - Rigual-Hernández, A. S. (2020)
The Southern Ocean is warming faster than the average global ocean and is particularly vulnerable to ocean acidification due to its low temperatures and moderate alkalinity. Coccolithophores are the most productive calcifying phytoplankton and an important component of Southern Ocean ecosystems. Laboratory observations on the most abundant coccolithophore, Emiliania huxleyi, suggest that this species is susceptible to variations in seawater carbonate chemistry, with consequent impacts in the carbon cycle. Whether anthropogenic environmental change during the industrial era has modified coccolithophore populations in the Southern Ocean, however, remains uncertain. This study analysed the coccolithophore assemblage composition and morphometric parameters of E. huxleyi coccoliths of a suite of Holocene-aged sediment samples from south of Tasmania. The analysis suggests that dissolution diminished the mass and length of E. huxleyi coccoliths in the sediments, but the thickness of the coccoliths was decoupled from dissolution allowing direct comparison of samples with different degree of preservation. The latitudinal distribution pattern of coccolith thickness mirrors the latitudinal environmental gradient in the surface layer, highlighting the importance of the geographic distribution of E. huxleyi morphotypes on the control of coccolith morphometrics. Additionally, comparison of the E. huxleyi coccolith assemblages in the sediments with those of annual subantarctic sediment trap records found that modern E. huxleyi coccoliths are 2% thinner than those from the pre-industrial era. The subtle variation in coccolith thickness contrasts sharply with earlier work that documented a pronounced reduction in shell calcification and consequent shell-weight decrease of 30-35% on the planktonic foraminifera Globigerina bulloides induced by ocean acidification. Results of this study underscore the varying sensitivity of different marine calcifying plankton groups to ongoing environmental change.